PERSEPSI SISWA TERHADAP PROSES PEMBELAJARAN SENI RUPA DI SMA NEGERI 1 JUNJUNG SIRIH KECAMATAN JUNJUNG SIRIH KABUPATEN SOLOK - DIENG YULIA PUTRI, Drs. Ajusril S, Dra. Ernis, M. Pd (Serupa The Journal of Art Education, 2013)
The purpose of this study describe: a) Perception of students on teacher learning method in Arts subjects at SMA Negeri 1 Uphold betel., B) Perception of students studying the subject ofthe media applied Arts teacher at SMAN 1 stand for betel, c) Perception Students Against pengelolaankelas in Arts subjects at SMA Negeri 1 Uphold Sirih.d) Students' perceptions of thelearning process evaluation study Arts subjects in SMA N 1 Uphold Betel, descriptive research is describing facts or circumstances which are to take place without any manipulation of the variables. Existing variables in this study are the circumstances in deskriptifkan Subjects Student Perceptions Toward Cultural Arts Division of Fine Arts at SMA Negeri 1 Uphold Betel. Key words : Students' perceptions and learning process